Bid’ah dan Khilafiyah dalam Perspektif Tarjih Muhammadiyah - Afifi Fauzi Abbas (IDRIS Darulfunun Institute, 2021)
The development of schools, universities and other social communities followed the dynamic progress of Islam. This development has provided patterns and variations of religious perspectives. Tarjih, as a process of understanding religious texts that have strong references to the Al-Quran and as-Sunnah is also understood by Muhammadiyah as a process of renewal (tajdid) or improvement (islah). Developments in culture and language that have changed over time have made some religious perspectives challenging to understand. The progress of time and technology has provided a new dimension to the misinterpretation of religious views regarding halal and haram in the name of modernization. Diversity and misinterpretation are also very much related to our understanding of bid'ah and khilafiyah. Khilafiyah is a diversity of perspectives that is not bid'ah. Tarjih and tajdid are dynamic and will always reject bid'ah and superstition because they are not based on the al-Quran and as-Sunnah. This article intends to discuss this matter.